BURST Imaging at High Field - Wilton, Benjamin (2004)
BURST is a fast single-shot imaging technique used in magnetic resonance imaging. Most previous implementations of BURST on whole body systems have been carried out at fields of 1.5T and lower. In this work BURST has been implemented on a 3T whole body system. The signal and attenuation characteristics are discussed, leading to an approximate expression for the optimum echo time.